2015
DOI: 10.1002/jmri.24870
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of errors in biexponential T2 measurements of the prostate

Abstract: Use of optimum echo times can substantially improve the precision of biexponential T2 measurements. This optimization is anticipated to improve prostate cancer characterization using T2 measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…While the LWF is estimated reliably, estimation of short and long T 2 components is affected by the underlying tissue fractions and the TE distribution sampled . By only fitting to the even echoes to correct for stimulated echoes, the effective TE‐spacing in this study was 50 msec, which may have impinged on the accuracy of estimation of the short T 2 components.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While the LWF is estimated reliably, estimation of short and long T 2 components is affected by the underlying tissue fractions and the TE distribution sampled . By only fitting to the even echoes to correct for stimulated echoes, the effective TE‐spacing in this study was 50 msec, which may have impinged on the accuracy of estimation of the short T 2 components.…”
Section: Discussionmentioning
confidence: 90%
“…T 2 relaxation properties of normal prostatic tissue show a decay pattern that is multiexponential . The short T 2 component has been ascribed to water associated with the cellular compartment (epithelial and stromal cells), while the long T 2 component reflects the luminal space.…”
mentioning
confidence: 99%
“…Although, multi-component T 2 in prostate has been shown before [6,7,8,9,10] only one recent study investigated the application of this technique for cancer diagnosis [10]; however, no direct correlation between MRI and histology has been published. In our study, we validated MR measurements with wholemount histology, and performed statistical analysis to assess the accuracy of this technique in the detection and grading of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of bi-exponential T 2 decay in prostate has previously been shown [6,7,8,9], and recently investigated for potential contribution to prostate cancer diagnosis [10]. In this study, we investigated the relationship between multi-exponential T 2 mapping and the histopathology of prostatic tissue through a direct comparison between MRI and wholemount histology.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been developed based on the assumption that glandular tissue of prostate is composed of water compartments of different sizes associated with multiple T 2 relaxation times. It has been demonstrated that T 2 decay curves obtained from prostate are mainly biexponential . One may expect that the biexponential T 2 decay of prostate is composed of one term with a longer T 2 attributed to the water protons residing inside the luminal space and another term with a shorter T 2 attributed to the water protons residing within the epithelial and stromal tissue.…”
mentioning
confidence: 99%